Establishment of interleukin‐18 time‐resolved fluorescence immunoassay and its preliminary application in liver disease. Issue 5 (15th March 2021) - Zhang, Li; Zhou, Xiumei; Dai, Yaping; Lv, Chunyan; Wu, Jian; Wu, Qingqing; Li, Ting; Wang, Yigang; Xia, Penguo; Pei, Hao; Huang, Biao
ABSTRACT: Background: To establish a time‐resolved fluorescence immunoassay of interleukin (IL)‐18 (IL‐18‐TRFIA) and detect its concentration in different liver disease serum samples. Methods: The IL‐18 coating antibody and the Eu 3+ ‐labeled detection antibody were used for the IL‐18‐TRFIA to detect serum IL‐18 concentration in patients with liver cancer, hepatitis B, hepatitis C, autoimmune hepatitis, fatty liver disease, and healthy controls. The double‐antibody sandwich method was used and methodological evaluation was performed. Results: The average intra‐ and inter‐assay coefficient of variation for IL‐18‐TRFIA was 4.80% and 5.90%, respectively. The average recovery rate was 106.19 ± 3.44%. The sensitivity (10.96 pg/mL) was higher than that obtained using the ELISA method (62.5 pg/mL). The detection range was 10.96–1000 pg/mL. IL‐6 and galectin‐3 did not cross‐react with IL‐18‐TRFIA. The serum concentration of IL‐18 was (776.99; 653.48–952.39 pg/mL) in hepatitis C, (911; 775.55–1130.03 pg/mL) in fatty liver, (1048.88; 730.04–1185.10 pg/mL) in liver cancer, and (949.12; 723.70–1160.28 pg/mL) in hepatitis B. Moreover, IL‐18 serum levels were significantly higher in patients than the healthy controls (483.09; 402.52–599.70/mL) ( p  < 0.0001). Autoimmune hepatitis with a serum IL‐18 concentration of 571.62; 502.47–730.31 pg/mL was not significantly different from the healthy controls ( p  > 0.05). Conclusion: We established a highly sensitive IL‐18‐TRFIA method that successfully detected serum IL‐18 concentrations in different liver diseases. Furthermore, IL‐18 serum concentration was higher in patients with liver cancer, hepatitis C, hepatitis B, and fatty liver disease compared to healthy controls. Abstract : Comparison of the serum IL‐18 concentrations between five groups of liver disease patients and healthy controls. The average concentration of IL‐18 in the serum of patients with liver cancer was the highest.